Supervision for today's schools - Oliva, Peter F.; Pawlas, George E. (New York : John Wiley and Sons, 1997)
This book is divided into six parts: nature of supervision; Leadership in instructional development; Leadership in curriculum development; Leadership in staff development; The summative dimension of teacher evaluation; and Instructional supervision: Evaluation and change.
Keywords: Education; School supervision; School supervision -- United States